The Death Anxiety and Demoralization in Patients With Acute Myocardial Infarction Admitted to Post Cardiac Care Units of Iran University of Medical Sciences in 2021 - Soheila Rahimi; Mehrnoosh Inanlou; Tahereh Najafi Ghezeljeh; Hamid Haghani (Iran University of Medical Sciences, 2023)
Background & Aims It is essential to pay attention to the psychological complications after a heart attack in line with other physiological complications. The proximity of these patients to death has caused death anxiety, which can weaken their morale. This study aims to determine death anxiety and demoralization in patients with acute myocardial infarction admitted to post-cardiac care units of the Iran University of Medical Sciences in 2021. Materials & Methods The present study is a descriptive cross-sectional study that was performed on 206 patients with myocardial infarction admitted to the educational-medical centers of Iran University of Medical Sciences in the first half of 2021. Data collection tools included the demographic profile form, Templer death anxiety questionnaire, and Kissane demoralization. Data were analyzed using SPSS software, version 20 and Pearson correlation coefficient, independent t test, and analysis of variance. Results Most patients in the study were male, married, and self-employed with a mean age of 57.97±12.49 years. The mean score of death anxiety in patients with myocardial infarction was 6.26±1.62 (moderate). Most patients (43.7%) had moderate death anxiety. The mean score of demoralization syndrome was 11.88±5.34 (severe). Most patients (60.7%) had severe demoralization syndrome. Conclusion The death anxiety of patients after myocardial infarction was moderate and their demoralization syndrome was severe, therefore it is necessary to pay attention to them and recognize the factors affecting nurses working in intensive care units and recommend being included in the training of care for these patients.